Multicenter Evaluation of a New Screening Test That Detects Clostridium difficile in Fecal Specimens - Zheng, L. (American Society for Microbiology, 2004)
Clostridium difficile causes approximately 25% of nosocomial antibiotic-associated diarrheas and most cases of pseudomembranous colitis. We evaluated C. DIFF CHEK, a new screening test that detects glutamate dehydrogenase of C. difficile. Our results showed that this test was comparable to PCR in sensitivity and specificity and outperformed bacterial culture.